Senescence-associated secretory phenotype in lung cancer: remodeling the tumor microenvironment for metastasis and immune suppression - Chen, Chen; Chen, Ji; Zhang, Yanling; Zhang, Qijun; Shi, Haixia (Frontiers in Oncology, 2025)
Cellular senescence exerts dual roles in lung cancer pathogenesis: initially suppressing tumorigenesis via p53/p21/p16-mediated cell cycle arrest, but promoting malignancy through the senescence-associated secretory phenotype (SASP). SASP secretes cytokines, proteases, and growth factors, reshaping the tumor microenvironment (TME) to drive immune evasion, metastasis, and therapy resistance. NF-κB activation induces APOBEC3B mutagenesis and PD-L1 overexpression, while mTOR signaling enhances glycolysis and OXPHOS to fuel tumor growth. Clinically, telomere attrition, p16/p21 expression, and SASP components serve as prognostic biomarkers. Therapeutic strategies target senescent cells and SASP. Future directions focus on single-cell multi-omics to decode senescence heterogeneity, spatially controlled drug delivery, and therapies targeting senescence-immune-metabolic crosstalk. By unraveling senescence’s dual regulatory mechanisms, this review highlights precision approaches to overcome resistance and improve lung cancer outcomes.